(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
This paper reports and analyzes the presence of large, seismic-scale, mass transport deposits (MTDs) recorded within the Guandacol Formation. These major submarine landslides seem to be connected with the occurrence of glacial episodes. The Guandacol Formation is part of the Paganzo Basin fill of Norwest Argentina (Fig. 1), and it is well known for recording several glacial cycles of the Late Paleozoic Ice Age. In this contribution we report and describe three major glacial/deglacial cycles (Fig. 1b) of Mississippian/Pennsylvanian age (Valdez et al., 2013). Outcrops of Guandacol Formation in Cerro Bola and Sierra de Maz (Cerro Guandacol) areas preserve those glacial cycles and each consists in the succession from non-glacial deltaic deposits to proglacial and thick mass-transport deposits (resedimented diamictites), which are the aim of this study, and finally postglacial marine varied strata, including sandy turbidites, shales with and without dropstones and some deltaic deposits (Milana et al., 2010; Dykstra et al., 2011). This study focuses on Sierra de Maz and Cerro Bola localities because they show very well exposed seismic-scale MTDs that otherwise would be quite difficult to see (Fig. 2a, b). Thus, these outcrops give the opportunity to compare many characteristics that are usually seen in seismic records, directly on the ground. On this sense, this contribution is mainly oriented to describe the facial and geometrical interrelations between these large MTDs (as there are many minor MTDs) and not the detailed internal architecture or their comparison to specific seismic features. The occurrence of these large MTDs can be explained by the large amounts of sediment delivered to the basin triggered by glacial- deglacial episodes. Due to the scarcity of well-exposed mega-scale MTD successions, a detailed study is being carried out since a few years. The result of detailed mapping of this rough terrain allow an excellent correlation between single MTDs, for several kilometers from Guandacol to Bola Hill outcrops (Fig. 3), and also portraying how a single MTD changes laterally when passing from a basin-margin environment (Guandacol Hill) to a basin-center environment (Bola Hill). The local Guandacol Formation shows three large glacial cycles that are mainly represented by single large MTDs and/or MTD composite intervals. The oldest MTD1 crops out completely in the Guandacol Hill, but only the upper part is present at Bola Hill (Fig. 4). MTD1 particular diagenesis and broad folds caused some authors to separate it from the Guandacol Formation, but we did not find any significant unconformity other than the normal upper relief between it and the following inter-MTD deposits. MTD2 is the largest and occurs as basin widens and more accommodation space is available. Reaching up to 200 m thick, it crops out continuously for more than 10 km in Bola Hill and 4 km in Guandacol Hill (Figs. 5, 6). The MTD3 is more complex due to its encroaching with large syn-sedimentary faults that we interpret as a large-scale slide scar associated to the MTD3 interval (Figs. 9, 10). This potential slide scar is associated with other elements as incised valleys or rilling at the scar surface, which have been observed in subsurface examples. Therefore one of the largest example of MTD successions and probably the best exposed worldwide is documented for the first time as a large, seismic-scale slide-scar cropping out in association to an MTD interval, with all the suite of sedimentary and deformational elements that might be expected for this play. Due to the fact these features are rarely exposed altogether, we expect this outcrop could be a world-class example to observe features cropping out that otherwise could be only studied indirectly from deep-water seismic surveys. This succession also serves as an example of how some sedimentary features could be easily mistaken by tectonic features when the scale of the sedimentary processes involves the discrete movement of large volumes (several km3) of semiconsolidated sedimentary units, as in the case presented here.